Enhancing antibiotic therapy through comprehensive pharmacokinetic/pharmacodynamic principles - Mohammad Sina Alikhani; Mohsen Nazari; Mohsen Nazari; Shima Hatamkhani (Frontiers in Cellular and Infection Microbiology)
Antibiotic therapy relies on understanding both pharmacokinetics (PK) and pharmacodynamics (PD), which respectively address drug absorption, distribution, and elimination, and the relationship between drug concentration and antimicrobial efficacy. This review synthesizes decades of research, drawing from in-vitro studies, in-vivo models, and clinical observations, to elucidate the temporal dynamics of antibiotic activity. We explore how these dynamics, including concentration-effect relationships and post antibiotic effects, inform the classification of antibiotics based on their PD profiles. Additionally, we discuss the pivotal role of PK/PD principles in determining optimal dosage regimens. By providing a comprehensive overview of PK/PD principles in antibiotic therapy, this review aims to enhance understanding and improve treatment outcomes in clinical practice.